COVID-19 retracted publications on retraction watch: A systematic survey of their pre-prints and citations. Issue 4 (April 2023) - Syed, Zainab; Syed, Fatema; Thabane, Lehana; Rodrigues, Myanca
Abstract: Background: Studies related to the coronavirus disease 2019 (COVID-19) were frequently published as pre-prints prior to undergoing peer-review. However, several publications were later retracted due to ethical concerns or study misconduct. Although these studies have been retracted, the availability of their corresponding pre-prints has never been formally investigated, and may result in the spread of misinformation if they are being used to inform decision-making. Methods: Our objective was to conduct a systematic survey of retracted COVID-19 publications listed on the Retraction Watch database as of August 15th, 2021. We assessed the availability of corresponding pre-prints for retracted publications, and documented the number of citations and online views. Results: Our study included 140 retracted COVID-19 publications, and we could not retrieve corresponding pre-prints for 132 retracted publications in our study (94%). Although we were unable to find the majority of pre-prints, they had already been disseminated, with a maximal citation count of 593 and Altmetric score of 558, 928. Conclusion: While it is reassuring that most corresponding pre-prints could not be retrieved, our study highlights the need for online platforms and journals to employ quality assurance methods to prevent the spread of misinformation through citation of retracted papers.